Concise English handbook - Kirkland, James W.; Dilworth, Collett B. (Boston : Houghton Mifflin, 1997)
This book is about: Composing the essay; Structuring sentences; Writing with precision and control; Punctuating mechanical; ...
Keywords: English language; Rhetoric; English language -- Grammar -- Handbooks, manuals, etc; English language -- Rhetoric -- Handbooks, manuals, etc